PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM: ANALISIS KONSEPSI, TUJUAN, MATERI, STRATEGI, DAN EVALUASI PEMBELAJARAN - Darmalinda; Fadriati, Fadriati (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2024)
The field of Islamic Religious Education serves as the main foundation in implementing Islamic Cultural History (SKI) in Elementary Islamic Schools (MI), Junior High Islamic Schools (MTs), and Senior High Islamic Schools (MA). This research aims to comprehend the concept of Islamic cultural history (SKI), the objectives of SKI learning, the content of SKI (in MI, MTs, and MA), teaching strategies for SKI, as well as the evaluation of SKI learning. The study adopts a qualitative descriptive research approach with document analysis. The findings reveal the necessity for the holistic development of SKI learning, involving more than mere memorization of knowledge. The coverage of SKI material needs to be expanded to ensure a profound understanding. The instructional practices of SKI in MI, MTs, and MA tend to lack student engagement, indicating the need for more innovative and captivating approaches. Evaluation of learning is also a focal point, with findings suggesting suboptimal implementation to enhance the quality of SKI learning. Therefore, recommendations are proposed to improve teaching strategies, develop engaging materials, and enhance evaluation methods to ensure that SKI learning achieves its desired goals.